Empirical Analysis of Financial Factors Influencing Profitability in Indonesian Tech Firms - Naibaho, Eldridge Elisha Halomoan (TEMA, 2025)
The Technology industry has been growing rapidly for the last 5 years and continues to improve the Indonesian economy. However, despite the conditions that support companies to increase profitability, there are still many companies that experience losses. This study aims to test and provide empirical evidence related to several internal company factors that can affect profitability. The object of this study is companies listed in the technology sector of the Indonesia Stock Exchange from 2020 to 2023. The samples obtained in the study are 12 companies with a total of 48 data points, with a panel regression test as the analysis method used in the study. The results showed that liquidity has a significant negative effect on profitability. Leverage has a significant positive effect on profitability. Company size has no significant effect on profitability. Asset growth has a significant positive effect on profitability. This study is useful for providing insight into the relationship between independent variables and dependent variables in a research model specifically designed to explain the phenomenon of profitability inconsistency in the rapidly growing technology sector.